ENT 530 Business Model Canvas: Marrybrown / Nur Aina Nadiah Mohammad Akmal ... [et al.] - Mohammad Akmal, Nur Aina Nadiah; Abdul Rahman, Nur Afifah; Ismail, Hafizul Hakim; Zaharuddin, Luqman Hakeem; Md Zuber, Muhammad Zulfadhli Syam; Badrul Hisham, Mohammad Fahmie; Shaffian, Nur Muhammad Alwaliaddin (2021)
Marrybrown is a fast-food restaurant. The concept of this restaurant is themed on Malaysian tastes because this is a company from Malaysia. As we all know, Marrybrown competitors like McDonald’s, Burger King, A&W, and others use the concept of American taste. For example, hamburgers are among the American foods. As for the business, Marrybrown provides special and delicious food for youths or students, working adults and families who want to eat a fast meal. This meal is consumed for those who want a filling and fast food. At the same time, it is in line with Malaysian tastes. The restaurant also offers reasonably priced, and large portions compared to competitors in the fast-food category. The target market for Marrybrown is for workers and students. For example, during lunch hour people need time service. In addition, those who want to create an event and do not have enough time for food preparation. Marrybrown branch locations are mostly in the city and it is strategic to attract the attention of their target market. It is prepared for a group of people, including the owners, bankers, creditors, suppliers, consumers, and staff. Marketing, operational, organizational, and financial plans are all included in this business plan.